Abundance of arthropod in the various intensity of pesticide applied on shallots crop Local Palu - Kasman Jaya; Ratnawati; Sylvia Sjam; Ade Rosmana; Untung Surapati Tresnaputra; Sri Sudewi (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Excessive use of pesticides confers several ecological and environmental consequences. In this research, we evaluated arthropod occurrence on shallot crops in Palu Valley, Central Sulawesi as an impact of pesticide application in different frequencies. Almost all farmers used synthetic pesticides for controlling pests and diseases where 46.7%, 43.3%, 10.0% of them applied in high, moderate, and low frequency, respectively. By comparing to the last application, the first reduced arthropod diversity index, evenness index, and abundance by 13.8%, 6.7%, and 70.6%, while the second by 7.3%, 2.3%, and 33.5%, respectively. Analysis of the dynamic abundance of pests and natural enemies in seven weeks observation indicated that the pests abundance at low and moderate levels was no different. Whereas predator abundance at low frequency was significantly different with moderate and high rate and between the last two not distinct and the presence of parasitoids was not observed at all, it means the natural enemies were susceptible to pesticides. These data showed the negative impact of pesticides application to arthropods including pests resistance and natural enemies lost; therefore it is necessary to minimize the use of pesticides and integrated pests.